Synthesis routes for enhanced piezoelectric properties in spark plasma sintered Ta-doped KNN ceramics. Issue 5 (May 2022) - Dubernet, Marion; Pitcher, Michael J.; Zaghrioui, Mustapha; Bah, Micka; Bustillo, Julien; Giovannelli, Fabien; Monot-Laffez, Isabelle
Abstract: Ta substitution in K0.5 Na0.5 NbO3 lead free piezoelectrics helps to prevent grain growth and has been shown to improve the piezoelectric properties but always leads to hetereogeneous microstructures. Two synthesis routes have been studied to prepare K0.5 Na0.5 Nb0.8 Ta0.2 O3 (KNNTa) substituted powders. Then highly densified KNNTa ceramics have been obtained by spark plasma sintering (SPS). The use of a synthesized oxide precursor Nb1.6 Ta0.4 O5 during the ceramic elaboration process clearly shows through accurate Rietveld study a successful Ta substitution with 92% of Amm2 K0.485(8) Na0.515(8) Nb0.819(6) Ta0.181(6) O3 phase, confirmed by SEM-EDS analysis and a more homogeneous chemical composition. This leads to enhanced electromechanical coupling coefficients with an improvement of 50% of k t, 15% for k p and low electrical losses, compared to the conventional synthesis method with a simple mixing of commercial precursors.